Methods of detection of adverse events in critical care: a protocol for a systematic review - Oleksa Rewa; Sandy Widder; Jocelyn Slemko; Janice Y Kung; Jay Gorman (BMJ Open)
Introduction Adverse events, defined as unintended patient harm contributed to by healthcare, continue to increase morbidity, mortality and cost. Critically ill patients are at high risk of adverse events; however, the optimal approach to detection in this setting is unknown. Numerous approaches have been used, including voluntary reporting, chart reviews and trigger tools. The objective of this systematic review is to gain insight into the capacity of individual methods to detect adverse events in the intensive care unit (ICU), to inform implementation, and to facilitate quality improvement.Methods and analysis Ovid MEDLINE, Ovid EMBASE, CINAHL, the Cochrane Library and Google Scholar were searched on 2 October 2023 for randomised controlled trials and observational studies evaluating the implementation or ongoing use of one or more systems of detection of adverse events in ICUs (neonatal to adult). Outcomes will include the total number of adverse events identified by detection method per 100 patient days (primary outcome), categories of adverse events, associated harm and whether detection informed quality improvement. A risk of bias assessment will be performed. The results will provide insight into each method’s capacity to detect adverse events in addition to their associated severity.Ethics and dissemination Ethics approval was not required as patient data will not be collected. A manuscript will be submitted to a peer-reviewed scientific journal.PROSPERO registration number CRD42024466584.